Legal Aspects of Implementing Confidentiality Protection of Customer Fund Deposits at BUMD Bank Lampung - Zulfi Diane Zaini; Yulia Hesti; Rivo Raihanza Passa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Bank secrecy is important because banks as trusted institutions are required to keep everything related to depositors and their deposits confidential. As for the legal protection process for the secrecy of customer funds depositing funds at BUMD Bank Lampung, namely the prevalence of bank operations involving the collection of public funds such as through current accounts, savings, deposits, and so on. Meanwhile, after collecting these funds, the bank needs to distribute these funds to the public, namely through the provision of credit. Other efforts, namely adequate recording of bank operations or transactions conducted by banks is a must. Suggestions for bank management, it is best to be careful in applying the principle of bank prudence, especially in receiving funds to be deposited by customers by asking customers for sources of funds, especially for large deposits, so that the bank can avoid attempts at banking crime. such as money laundering.